2008
DOI: 10.1175/2007jamc1565.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Synoptic Variations in Near-Surface Air Temperature Lapse Rates in a Mountainous Basin

Abstract: To accurately estimate near-surface (2 m) air temperatures in a mountainous region for hydrologic prediction models and other investigations of environmental processes, the authors evaluated daily and seasonal variations (with the consideration of different weather types) of surface air temperature lapse rates at a spatial scale of 10 000 km 2 in south-central Idaho. Near-surface air temperature data (T max , T min , and T avg ) from 14 meteorological stations were used to compute daily lapse rates from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
230
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(264 citation statements)
references
References 35 publications
21
230
3
1
Order By: Relevance
“…The typically reported nocturnal cold air drainage reducing lapse rates at night, along with steeper lapse rates during the day, in summer, or associated with STEFAN W. GRAB / 511 enhanced cyclonic activity (low pressure and high relative vorticity) (e.g. Pepin, 2001;Blandford et al, 2008;Gillies et al, 2010;Bianco et al, 2011), are all to a considerable extent masked along the Drakensberg escarpment. This is owing to regional-scale westerly winds (particularly during the austral winter and spring) bringing dry air over and down the Great Escarpment, eradicating clouds and thus steepening lapse rates towards the upper escarpment zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The typically reported nocturnal cold air drainage reducing lapse rates at night, along with steeper lapse rates during the day, in summer, or associated with STEFAN W. GRAB / 511 enhanced cyclonic activity (low pressure and high relative vorticity) (e.g. Pepin, 2001;Blandford et al, 2008;Gillies et al, 2010;Bianco et al, 2011), are all to a considerable extent masked along the Drakensberg escarpment. This is owing to regional-scale westerly winds (particularly during the austral winter and spring) bringing dry air over and down the Great Escarpment, eradicating clouds and thus steepening lapse rates towards the upper escarpment zone.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examining lapse rates in mountain environments are typically at a regional scale (Ͼ10 km) (e.g. Fang and Yoda, 1988;Pepin, 2001;Blandford et al, 2008), yet it is argued that finer-scale (Ͻ10 km) analyses and modeling at the local valley scale may provide for smaller temperature prediction errors (e.g. Bolstad et al, 1998;Pagés and Miró, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Lapse rate' is defined as 'the decrease of an atmospheric variable with height, the variable being temperature, unless otherwise specified' 12 and it often refers to the environmental lapse rate or free atmospheric lapse rate in a vertical profile of the atmosphere 13 . Lapse rate can also refer to reduction of temperature at the different elevations at the surface of a mountainous terrain where it is termed 'near-surface lapse rate' 14,15 . The employment of environmental lapse rates to estimate the surface conditions has an implicit assumption that the terrain and surface processes are insignificant in determining surface temperatures, which is not a good approximation for temperature estimations in mountainous basins 14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Many aspectes of elevation dependencies of surface temperature variations along the mountain slopes have been investigated 25 across various mountain ranges of the world (Richner and Phillips, 1984;Rolland, 2003;Pepin and Seidel, 2005;Blandford et al,2008;Kattel et al, 2013). Comparative studies of free air and surface temperature variations have amply demonstrated the significant differences between the two (Pepin and Losleben, 2002;Pepin and Seidel, 2005).…”
mentioning
confidence: 99%